STRATEGIES TO COMBAT HUNGER AND THE ARTICULATION OF LOCAL PUBLIC POLICIES IN PERNAMBUCO - de Moraes, Ana Paula; Outtes, Natalia; da Silva, Ana Paula Gomes; da Silva, Catarine Santos; da Silva, Maria Zênia Tavares; Andrade, Horasa Maria Lima da Silva (Seven Editora, 2026)
This study reports on the process of implementing Community Kitchens in Pernambuco within the context of the Food and Nutrition Security and Food Sovereignty Policy. The main objective is to assess how a program formulated by the state government, in partnership with municipalities, with its own specific features of management, target population, and social control—shaped by institutional arrangements reflecting local perspectives and interests—can articulate multiple public policies at the territorial level. An exploratory and descriptive approach was adopted, based on a qualitative research design. The results indicate that only a small number of community kitchens have effectively articulated local public policies. We conclude that the integration of public policies at the municipal level is essential for the consolidation of these facilities. We recommend that the program encourage integration with other municipal food policy initiatives in order to strengthen governance and participatory management. DOI: https://doi.org/10.56238/sevened2026.002-010